Out of my mind - Draper, Sharon M. (Sharon Mills) (New York : Atheneum Books for Young Readers, 2010)
Considered by many to be mentally retarded, a brilliant, impatient fifth-grader with cerebral palsy discovers a technological device that will allow her to speak for the first time.